Chemical Reactivity, Dipole Moment and First Hyperpolarizability of Aristolochic Acid I - Joshi, Bhawani Datta (Journal of Institute of Science and Technology, 2016)
Aristolochic acids (AAs) have been used in the treatment of oedema in Chinese herb medicine since long ago. In this paper, molecular electrostatic potential, chemical reactivity and non linear optical properties of aristolochic acid I (AA I) have been analyzed using density functional theory employing 6-311++G(d,p) basis set. The chemical reactivity of the molecule has been explained with the help of chemical reactivity descriptors, molar refractivity and the molecular electrostatic potential surface (ESP). The calculated dipole moment and first order hyperpolarizability show that the molecule possesses non-linear optical property. Journal of Institute of Science and Technology Volume 21, Issue 1, August 2016, page: 1-9